A Dynamic Congestion Control Scheme for safety applications in vehicular ad hoc networks. (November 2018) - Qureshi, Kashif Naseer; Abdullah, Abdul Hanan; Kaiwartya, Omprakash; Iqbal, Saleem; Butt, Rizwan Aslam; Bashir, Faisal
Abstract: In recent years, various types of applications have emerged from Vehicular Ad hoc Networks (VANETs) for safety, infotainment, rescue and security purposes. Safety applications have their own strict communication requirements, and they require reliable and timely data communication within networks. Due to a variety of network applications, safety applications have been negatively impacted by communication channel congestion issues. Channel congestion leads to packet loss, delay and unreliability issues, and has a serious impact on vehicular traffic, including road accidents, road jams, and wrong traffic decisions. In addressing these issues, this paper's authors have proposed a Dynamic Congestion Control Scheme (DCCS) as a means of reliable and timely data delivery, in safety applications. The proposed scheme is designed for communication channels, as a means of broadcasting safety messages, and to ensure the reliable and timely delivery of messages to all neighbours in a network. The DCCS scheme is designed for inter-vehicle communication, without fixed infrastructure. Comprehensive simulation is conducted, in order to evaluate the performance of a proposed scheme, and to compare it with other state of the art schemes.